Merambah Etika Protestan dan Sosiologi Nilai Max Weber “Korelasi Antara Calvinisme dengan Spirit Kapitalisme” - Marde Christian Stenly Mawikere; Sudiria Hura (Peneliti.net, 2022)
This study traces the traces of the Sociology of Religion theory (classic) from Max Weber which he described in his best-selling book entitled